Flavokawain A Reduces Tumor-Initiating Properties and Stemness of Prostate Cancer - Song, Liankun; Mino, Merci; Yamak, Jana; Nguyen, Vyvyan; Lopez, Derron; Pham, Victor; Fazelpour, Ali; Le, Vinh; Fu, Dongjun; Tippin, Matthew; Uchio, Edward; Zi, Xiaolin (Frontiers in Oncology, 2022)
We have previously demonstrated the in vivo chemopreventive efficacy of flavokawain A (FKA), a novel chalcone from the kava plant, in prostate carcinogenesis models. However, the mechanisms of the anticarcinogenic effects of FKA remain largely unknown. We evaluated the effect of FKA on prostate tumor spheroid formation by prostate cancer stem cells, which were sorted out from CD44+/CD133+ prostate cancer cells 22Rv1 and DU145. FKA treatment significantly decreased both the size and numbers of the tumor spheroids over different generations of spheroid passages. In addition, the dietary feeding of FKA-formulated food to Nonobese diabetic/severe combined immunodeficiency (NOD/SCID) mice bearing CD44+/CD133+ 22Rv1 xenograft tumors resulted in a significant reduction of tumor growth compared to those fed with vehicle control food–fed mice. Furthermore, the expression of stem cell markers, such as Nanog, Oct4, and CD44, were markedly downregulated in both tumor spheroids and tumor tissues. We also observed that FKA inhibits Ubc12 neddylation, c-Myc, and keratin-8 expression in both CD44+/CD133+ prostate tumor spheroids and xenograft tumors. Our results suggest that FKA can reduce the tumor-initiating properties and stemness of prostate cancer, which provides a new mechanism for the chemoprevention efficacy of FKA.